2006
DOI: 10.5194/aab-49-340-2006
|View full text |Cite
|
Sign up to set email alerts
|

The content of polyunsaturated fatty acids in intramuscular fat of beef cattle in different breeds and crossbreeds

Abstract: Abstract. The effect of crossbreeding on the content of polyunsaturated fatty acids (PUFA) in intramuscular adipose tissue of the Musculus longissimus pars thoracis of slaughter bulls was studied. The differences among 8 genotypes of bulls was most significant (p<0.01) in C18:3, C20:4, C22:4, C22:5 and C22:6. The content of linolenic acid (C18:3) in the Czech Spotted Cattle (control group) was 0.526%, the highest in the Czech Spotted x Piedmont cattle crosses (0.659 %), and the lowest in crosses with the Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…However, recently published studies evaluating meat production showed a higher growth rate of M bulls (Chládek et al, 2005) and none or minimum differences in carcass composition (Šubrt and Mikšík, 2002). Few works have dealt with the comparison of the fatty acid (FA) profile of dual-purpose breeds of Simmental origin (Reichardt et al, 1997;Kirchheim et al, 1998;Hollo et al, 2001;Petrič et al, 2005;Šubrt et al, 2006), which are "the pillar" of milk-producing cattle population in Central Europe. According to several authors, selective breeding could be applied to improve the fatty acid profile of intramuscular fat (Malau-Aduli et al, 1998;Laborde et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, recently published studies evaluating meat production showed a higher growth rate of M bulls (Chládek et al, 2005) and none or minimum differences in carcass composition (Šubrt and Mikšík, 2002). Few works have dealt with the comparison of the fatty acid (FA) profile of dual-purpose breeds of Simmental origin (Reichardt et al, 1997;Kirchheim et al, 1998;Hollo et al, 2001;Petrič et al, 2005;Šubrt et al, 2006), which are "the pillar" of milk-producing cattle population in Central Europe. According to several authors, selective breeding could be applied to improve the fatty acid profile of intramuscular fat (Malau-Aduli et al, 1998;Laborde et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Subrt et al (2006) reported that higher levels of total MUFAs could be associated with the ability of the breeds and cattle genotypes to deposit intramuscularly adipose tissue. Samkova et al (2012) similarly found an increasing trend for various breeds, that is, Holstein, Jersey, Brown Swiss, Ayrshire and Montbéliarde, with higher FA from early to the end of the lactation period.…”
Section: Figurementioning
confidence: 99%
“…In turn, IMF is the chemically estimated fat content of meat; the terms marbling and IMF are commonly used alternatively. This characteristic presents considerable variability both between (Chambaz et al, 2001;Šurbt et al, 2006) and within breed populations (Węglarz, 2010a) and among muscle types depending on their anatomy and the physiological role played (Rhee et al, 2004, Searls et al, 2005.…”
Section: Introductionmentioning
confidence: 99%